Table of Content - -, (Journal of Risk and Crisis Management, 2024)
Table of Content:1. Risks of Electronic Payment Services and Their Relationship to Cybercrimes: An Applied Study  on the Payment Services Sector in the Kingdom of Saudi Arabia (July to August 2024)Ms. Nada Mansour Bin Dawood, Dr. Al-Faisal Abdul-Hamid Muhammad, Dr. Fayez Ali Jarad2. The Role of Graphic Design in Risk and Crisis ManagementDr. Mohamed Abdelaziz Mohamed3. The role of administrative leadership in crisis management in government hospitals in Saudi Arabia during the (Covid -19)Mr. Hathloul Saleh Alshammari4. The effect of strategic planning in improving the efficiency of crisis management in Jordanian industrial companiesMr. Salem Mohammed Al-Hababi
Keywords: Journal of Risk and Crisis Management